A composite hydrogel based on biological ionic liquid polymerization and preparation method thereof

Through the composite hydrogel based on bioion liquids, the free radical polymerization of methacrylylated hyaluronic acid and oxidized hyaluronic acid and imine bond interweaving of ε-polylysine, the short-term antibacterial effect of wound dressing is solved and the short-term and simplex effect of wound dressing is solved. Multifunctional requirements achieve efficient wound healing and safety improvement.

CN116173290BActive Publication Date: 2025-01-14SHENYANG PHARMA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310049968.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2025-01-14
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

Existing wound dressings lose antibacterial effects in a short period of time and are difficult to meet the needs of biocompatibility, mechanical strength, appropriate tissue adhesion, ease of removal and environmental moistness, resulting in the risk of delayed wound healing or complications.

Method used

Using a composite hydrogel based on bioion liquid polymerization, the free radical polymerization of methacrylated hyaluronic acid and oxidized hyaluronic acid and imine bonds of ε-polylysine are interwoven to form a three-dimensional network structure and through Preparation of ultraviolet cross-linking, combining photoinitiators and photocrosslinking agents, achieve antibacterial and hemostatic effects.

Benefits of technology

The prepared composite hydrogel has good biocompatibility, antibacterial activity and hemostasis ability, promotes wound healing, and maintains long-term antibacterial effect in humid environments, significantly improving wound healing speed and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004057447070000081
    Figure BDA0004057447070000081
  • Figure BDA0004057447070000091
    Figure BDA0004057447070000091
  • Figure BDA0004057447070000092
    Figure BDA0004057447070000092
Patent Text Reader

Abstract

The present invention relates to a composite hydrogel based on biological ionic liquid polymerization and a preparation method thereof, and belongs to the field of material technology. A composite hydrogel based on biological ionic liquid polymerization, the composite hydrogel has a three-dimensional network structure, and the three-dimensional network structure is interwoven by two networks: one: a network formed by polymerization of biological ionic liquid and methacryloyl hyaluronic acid, and self-crosslinking of methacryloyl hyaluronic acid; the other: a network formed by oxidized hyaluronic acid and ε-polylysine through an imine bond. The hydrogel prepared by the present invention can be applied to the bleeding part, and can play a role in rapid hemostasis, long-term antibacterial and thus promoting wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite hydrogel based on biological ionic liquid polymerization and a preparation method thereof, belonging to the technical field of materials. Background Art

[0002] Wound healing is a complex and dynamic process that includes four consecutive but overlapping stages: hemostasis, inflammation, proliferation, and remodeling. In this process, uncontrolled bleeding, bacterial infection, and persistent inflammation are the most fatal problems, causing wound pain, delayed healing, and even death. On the one hand, hemostasis is crucial because heavy bleeding in a short period of time can cause shock or other serious complications. On the other hand, bacteria can cause tissue damage by releasing endotoxins, increasing the release of proinflammatory cytokines or exotoxins, and preventing angiogenesis and epithelialization. Therefore, it is of great significance to design a wound dressing that can quickly control bleeding and has an antibacterial effect.

[0003] A common approach to developing antimicrobial wound dressings is to encapsulate or adsorb the antimicrobial agent onto the dressing. However, one of the issues is the leaching of the antimicrobial drug. The dressing loses its antimicrobial effect within a short period of time, exposing the wound to high concentrations of the drug and causing side effects to the patient. This has promoted the construction of wound dressings with long-lasting intrinsic antimicrobial activity. In addition to the above requirements, it is also desirable to develop wound dressings with good biocompatibility, suitable mechanical strength and tissue adhesion, ease of use, easy removal, moist environment maintenance, and good water vapor permeability. Therefore, designing an effective composite wound dressing is a major challenge, especially to ensure a successful combination of the required properties.

[0004] Hydrogels are three-dimensional polymer networks made of hydrophilic natural or synthetic polymers, which are made insoluble in water by physical or chemical crosslinking, and have the potential to become wound dressings. The reasons are as follows: First, the three-dimensional network can absorb and retain a large amount of water, maintaining a humid environment. Second, hydrogels can absorb tissue exudate, rehydrate necrotic tissue, and enhance autolysis and debridement. In addition, hydrogels can promote the formation of thrombi and form a physical barrier at the bleeding site, thereby quickly stopping bleeding. Hydrogels are similar to extracellular matrix and have significant biocompatibility. Their porous structure facilitates the transport of oxygen to the injured area. Because oxygen is necessary for fibroblasts to secrete collagen and extracellular matrix compounds, angiogenesis, and tissue formation. Therefore, hydrogels have a wide range of applications in the biomedical field. Summary of the invention

[0005] The technical problem to be solved by the present invention is to design a wound dressing with multiple functions, ensure the successful combination of required properties, and prepare it into a hydrogel.

[0006] A composite hydrogel based on biological ionic liquid polymerization, wherein the composite hydrogel has a three-dimensional network structure, and the three-dimensional network structure is interwoven by two networks:

[0007] First: the polymerization of biological ionic liquid and methacryloyl hyaluronic acid, and the network formed by self-crosslinking of methacryloyl hyaluronic acid;

[0008] Second: The network formed by oxidized hyaluronic acid and ε-polylysine through imine bonds.

[0009] In the above network, the biological ionic liquid and the methacryloyl hyaluronic acid undergo free radical polymerization to polymerize, opening the unsaturated double bonds in the structure to form biological ionic liquid-CH2-CH2-methacryloyl hyaluronic acid macromolecules. Similarly, the methacryloyl hyaluronic acid also undergoes free radical polymerization to self-crosslink to form methacryloyl hyaluronic acid-CH2-CH2-methacryloyl hyaluronic acid macromolecules.

[0010] Preferably, the composite hydrogel is prepared by in-situ crosslinking with ultraviolet light using methacryloyl hyaluronic acid, oxidized hyaluronic acid, biological ionic liquid and ε-polylysine as raw materials.

[0011] Furthermore, the mass ratio of the methacryloyl hyaluronic acid to the oxidized hyaluronic acid is 7:1 to 7:2; the mass ratio of the methacryloyl hyaluronic acid to ε-polylysine is 7:1 to 7:2; the mass ratio of the methacryloyl hyaluronic acid to the biological ionic liquid is 7:1 to 7:37.5.

[0012] Furthermore, preferably, the mass ratio of the methacryloyl hyaluronic acid to the oxidized hyaluronic acid is 7:2; the mass ratio of the methacryloyl hyaluronic acid to the ε-polylysine is 7:2; and the mass ratio of the methacryloyl hyaluronic acid to the biological ionic liquid is 7:37.5.

[0013] Preferably, the raw material further comprises water. Further, the mass ratio of the biological ionic liquid to water is 1:49 to 3:1. Further, preferably, the mass ratio of the biological ionic liquid to water is 3:1.

[0014] When preparing the composite hydrogel based on bio-ionic liquid polymerization of the present invention, a photoinitiator and a photocrosslinker required for photocrosslinking are added. The amount of the photoinitiator and the photocrosslinker is sufficient to allow the photocrosslinking reaction to react fully, and the amount can be determined by those skilled in the art.

[0015] Preferably, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the photocrosslinker is polyethylene glycol diacrylate.

[0016] The composite hydrogel of the present invention is prepared by ultraviolet crosslinking using methacryloyl hyaluronic acid, oxidized hyaluronic acid, biological ionic liquid and ε-polylysine (including water if necessary) as raw materials. The composite hydrogel has a three-dimensional network structure, which is mainly formed by two networks: one is the network formed by the polymerization of biological ionic liquid and methacryloyl hyaluronic acid, and the self-crosslinking of methacryloyl hyaluronic acid, which is realized by photocrosslinking; the other is the network formed by oxidized hyaluronic acid and ε-polylysine through imine bonds, which is realized by Schiff base reaction. The prepared composite hydrogel has good biocompatibility, antibacterial activity, hemostasis, and can also promote wound healing.

[0017] Preferably, the composite hydrogel is prepared by the following steps:

[0018] The biological ionic liquid is diluted with water and stirred evenly to obtain a clear and uniform solution A as a solvent for the reaction; methacrylylated hyaluronic acid and oxidized hyaluronic acid are mixed evenly to obtain a mixture B; the mixture B is slowly added to the solution A and stirred evenly to obtain a mixture C; the ε-polylysine solution is added to the mixture C and mixed evenly to obtain a mixture D; a photoinitiator and a photocrosslinker are added to the mixture D and mixed evenly to obtain a mixture E; the mixture E is placed under an ultraviolet lamp for crosslinking.

[0019] Furthermore, the photocrosslinking time is 600 s and the wavelength is 365 nm.

[0020] Furthermore, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the photocrosslinker is polyethylene glycol diacrylate.

[0021] Furthermore, the concentration of the ε-polylysine solution is 0.5 g / mL.

[0022] Furthermore, the biological ionic liquid is prepared by the following method: choline hydroxide and acrylic acid are mixed and reacted; the product is washed with an organic solvent for multiple times and vacuum dried to obtain;

[0023] The molar ratio of choline hydroxide to acrylic acid is 1:1 to 1:2, the reaction temperature is 4° C., and the reaction time is 24 hours; and the organic solvent is ether and ethyl acetate.

[0024] Furthermore, the methacryloyl hyaluronic acid is prepared by the following method: methacrylic anhydride is added to a hyaluronic acid solution for reaction, the reaction condition is an ice bath, and the pH of the reaction system is maintained in the range of 8-10; after the reaction is completed, the reaction solution is dialyzed and freeze-dried to obtain,

[0025] The concentration of hyaluronic acid in the hyaluronic acid solution is 0.1-0.2 g / mL, and the hyaluronic acid solution is a mixed solution composed of water and N,N-dimethylformamide in a volume ratio of 3:2; the molar ratio of hyaluronic acid to methacrylic anhydride is 1:3-1:10.

[0026] Furthermore, the grafting rate of the methacryloyl hyaluronic acid is 12%-30%; most preferably, the grafting rate is 22%.

[0027] Furthermore, the oxidized hyaluronic acid is prepared by the following method: sodium periodate is added to a hyaluronic acid aqueous solution for reaction at room temperature and in the dark; after the reaction is completed, the reaction solution is dialyzed and freeze-dried to obtain,

[0028] The concentration of hyaluronic acid in the hyaluronic acid aqueous solution is 0.1-0.2 g / mL, and the molar ratio of hyaluronic acid to sodium periodate is 1:0.25-1:1.

[0029] Furthermore, the oxidation degree of the oxidized hyaluronic acid is 20%-80%; most preferably, the oxidation degree is 30%.

[0030] In one aspect, the present invention provides the use of the composite hydrogel based on biological ionic liquid polymerization as a wound healing dressing.

[0031] The beneficial effects of the present invention are as follows: the present invention relates to a multifunctional composite hydrogel based on bio-ionic liquid polymerization and a preparation method thereof. The multifunctional composite hydrogel is a hydrogel prepared by ultraviolet crosslinking using synthetic methacryloyl hyaluronic acid, oxidized hyaluronic acid, bio-ionic liquid and ε-polylysine as raw materials, and has good hemostatic and antibacterial abilities and can promote wound healing. Hyaluronic acid derivatives have the characteristics of promoting coagulation and wound healing. ε-Polylysine has long-lasting broad-spectrum antibacterial properties and can also be combined with aldehyde groups through Schiff base reactions. Choline-based bio-ionic liquids are structural precursors of the phospholipid bilayer in the cell membrane, and cross-linking them to polymers can significantly improve the adhesion of the polymers. In addition, a humid environment is also conducive to wound healing. The hydrogel prepared by the present invention can be applied to the bleeding part, and can play a role in rapid hemostasis, long-term antibacterial and thus promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The NMR spectrum and structural formula of the biological ionic liquid in Example 1 are shown.

[0033] Figure 2 The NMR spectrum and structural formula of the methacryloyl hyaluronic acid in Example 1.

[0034] Figure 3 1 is the NMR spectrum and structural formula of the oxidized hyaluronic acid in Example 1.

[0035] Figure 4 This is the NMR spectrum of the composite hydrogel prepared in Example 1.

[0036] Figure 5 The synthetic flow chart of the composite hydrogel prepared in Examples 1, 2, 3, and 4.

[0037] Figure 6 This is a microstructure image of the composite hydrogel prepared in Example 1 under a scanning electron microscope.

[0038] Figure 7 The curves showing the swelling ratio of the composite hydrogels prepared in Examples 1, 2, 3 and 4 changing with time.

[0039] Figure 8 The porosity and water vapor permeability of the composite hydrogels prepared in Examples 1, 2, 3, and 4.

[0040] Fig. 9 The hemolysis rate of the composite hydrogel prepared in Examples 1, 2, 3, and 4.

[0041] Fig.10 This is a visual diagram of the antibacterial effect of the composite hydrogel prepared in Examples 1, 2, 3, and 4 on Escherichia coli and Staphylococcus aureus.

[0042] Fig.11 It is the in vitro coagulation index of the composite hydrogel prepared in Examples 1, 2, 3, and 4.

[0043] Fig.12 The amount of blood loss and the time of hemostasis at the tail amputation site when the composite hydrogel prepared in Example 1 was applied to a rat tail amputation model.

[0044] Fig.13 The composite hydrogel prepared in Example 1 was applied to the wound on the back of rats, and the wound healing rates on days 0, 3, 6, 9, 12 and 15 were measured. DETAILED DESCRIPTION

[0045] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0046] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0047] One of the specific implementations:

[0048] 1. A biological ionic liquid synthesized by a new method, wherein the biological ionic liquid is prepared by the following steps:

[0049] (A) mixing choline hydroxide and acrylic acid to react;

[0050] (B) The product is washed with an organic solvent for multiple times and dried in vacuum.

[0051] In the step (A), the molar ratio of choline hydroxide to acrylic acid is 1:1-1:2, and the reaction temperature is 4° C. and the reaction time is 24 hours.

[0052] The organic solvent in step (B) is ether or ethyl acetate.

[0053] 2. A method for synthesizing methacryloyl hyaluronic acid, wherein the methacryloyl hyaluronic acid is synthesized by the following steps:

[0054] (A) dissolving hyaluronic acid in deionized water to obtain a mixed solution A;

[0055] (B) adding N,N-dimethylformamide to the mixed solution A and stirring evenly to obtain a mixed solution B;

[0056] (C) adding methacrylic anhydride to the mixed solution B to react;

[0057] (D) After the reaction is completed, the reaction solution is dialyzed and freeze-dried to obtain the product.

[0058] The concentration of hyaluronic acid in step (A) is 0.1-0.2 g / mL.

[0059] In the step (B), the volume ratio of water to N,N-dimethylformamide is 3:2.

[0060] In the step (C), the molar ratio of hyaluronic acid to methacrylic anhydride is 1:3-1:10, the reaction condition is an ice bath, the reaction time is 24 hours, and the pH of the system is maintained in the range of 8-10 during the reaction.

[0061] In the step (D), the dialysis time is 3 days, and the product is stored at room temperature.

[0062] 3. A method for synthesizing oxidized hyaluronic acid, wherein the oxidized hyaluronic acid is prepared by the following steps:

[0063] (A) dissolving hyaluronic acid in deionized water to obtain a mixed solution A;

[0064] (B) adding sodium periodate to the mixed solution A to react;

[0065] (C) After the reaction is completed, the reaction solution is dialyzed and freeze-dried to obtain the product.

[0066] In the step (A), the concentration of hyaluronic acid is 0.1-0.2 g / mL, and the molar ratio of hyaluronic acid to methacrylic anhydride is 1:0.25-1:1.

[0067] The reaction conditions in step (B) are room temperature in the dark, and the reaction time is 2 hours.

[0068] In the step (C), the dialysis time is 3 days, and the product is stored at room temperature.

[0069] 4. A method for synthesizing a composite hydrogel for wound antibacterial and hemostasis, wherein the composite hydrogel is prepared by the following steps:

[0070] (A) diluting the bio-ionic liquid with purified water and stirring evenly to obtain a clear and uniform solution A as a solvent for the reaction;

[0071] (B) uniformly mixing the methacrylylated hyaluronic acid and the oxidized hyaluronic acid to obtain a mixture B;

[0072] (C) slowly adding mixture B to solution A and stirring to obtain mixture C;

[0073] (D) adding the ε-polylysine solution to the mixture C and mixing them uniformly to obtain a mixture D;

[0074] (E) adding a photoinitiator and a photocrosslinker to the mixture D, and mixing them uniformly to obtain a mixture E;

[0075] (F) placing the mixture E under ultraviolet light for cross-linking to obtain the product.

[0076] In the step (A), in solution A, the mass ratio of biological ionic liquid to water is 1:49 to 3:1, preferably 3:1; the mass ratio of methacryloyl hyaluronic acid to biological ionic liquid is 7:1 to 7:37.5, preferably 7:37.5.

[0077] In the step (B), the hyaluronic acid is methacrylated with a grafting rate of 12%-30%, preferably 22%; and the hyaluronic acid is oxidized with an oxidation degree of 20%-80%, preferably 30%.

[0078] In the step (B), the mass ratio of methacryloyl hyaluronic acid to oxidized hyaluronic acid is 7:1 to 7:2, and the preferred mass ratio is 7:2.

[0079] In the step (D), the ε-polylysine solution (0.5 g / mL) is obtained by dissolving ε-polylysine in purified water, and the mass ratio of methacryloyl hyaluronic acid to ε-polylysine is 7:1 to 7:2, with a preferred mass ratio of 7:2.

[0080] In the step (E), the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the photocrosslinker is polyethylene glycol diacrylate.

[0081] The crosslinking in the step (F) refers to crosslinking by ultraviolet light, the time is 600s-1200s, the wavelength is 365nm, and the optimal time is 600s.

[0082] Example 1

[0083] 1. Preparation of biological ionic liquids

[0084] (1) Choline hydroxide (8.096 g) was slowly added to acrylic acid (2.219 g), and the mixture was reacted at 4° C. for 24 h. The mixture was then washed with ether and ethyl acetate several times, and the purified product was dried under vacuum and stored at room temperature.

[0085] (2) Take 5.00 mg of biological ionic liquid and dissolve it in D2O (500 μL). Use nuclear magnetic resonance spectrometer to record the sample 1 HNMR spectrum.

[0086] (3) 1 H NMR ( Figure 1 ), the peaks of hydrogen atoms in the acrylate groups at 5.53-6.04 ppm confirmed the successful synthesis of choline hydroxide.

[0087] 2. Preparation of Methacryloyl Hyaluronic Acid

[0088] (1) Weigh hyaluronic acid (2.0 g) and completely dissolve it in 200 mL of distilled water. Then, add 135 mL of N,N-dimethylformamide. React in an ice bath at 4°C, and add 2.46 g of methacrylic anhydride to the solution. At the same time, use 2M NaOH to maintain the pH value of the solution at 8-9. Next, transfer the obtained solution to a dialysis bag (8-14 kDa) and dialyze it against deionized water for 72 hours. Finally, freeze-dry the purified product and store it at room temperature.

[0089] (2) Take 5.00 mg of the prepared methacryloyl hyaluronic acid and dissolve it in D2O (500 μL). Record the sample's 1 H NMR spectrum.

[0090] (3) 1 H NMR ( Figure 2), the hyaluronic acid grafted with methacrylic anhydride will show two new signal peaks at around δ=6.06ppm and 5.63ppm, and a very high signal peak at around δ=1.83ppm, which are the NMR peaks of double bond hydrogen on the methacrylate group and the NMR peaks of methyl hydrogen, respectively. This proves that the hyaluronic acid has been successfully grafted with methacrylate groups, and the grafting rate is 22%.

[0091] 3. Preparation of Oxidized Hyaluronic Acid

[0092] (1) Weigh hyaluronic acid (2.0 g) and completely dissolve it in 200 mL of distilled water. React at room temperature in the dark, add 0.535 g of sodium periodate to the solution, and react for 2 h. To stop the reaction, add excess ethylene glycol (1.0 g) to the reaction solution and stir for another 1 h. Next, transfer the resulting solution to a dialysis bag (8-14 kDa) and dialyze against deionized water for 72 h. Finally, freeze-dry the purified product and store it at room temperature.

[0093] (2) Take 5.00 mg of oxidized hyaluronic acid and dissolve it in D2O (500 μL). Record the sample's 1 HNMR spectrum.

[0094] (3) 1 H NMR ( Figure 3 ), compared with hyaluronic acid, oxidized hyaluronic acid has new chemical shifts at 4.87, 4.98 and 5.08 ppm ( Figure 3 ), indicating that hyaluronic acid has been successfully oxidized and the degree of oxidation is 30%.

[0095] 4. Preparation and characterization of composite hydrogels

[0096] 1. Preparation of composite hydrogel

[0097] (1) Methacryloyl hyaluronic acid (1.4 g) and oxidized hyaluronic acid (0.4 g) were dissolved in 10 g of bio-ionic liquid solution (prepared by 7.5 g of bio-ionic liquid and 2.5 g of water) at room temperature. After stirring evenly, ε-polylysine solution (0.5 g / mL, 800 μL) was added. Secondly, polyethylene glycol diacrylate (120 μL) and 1-hydroxycyclohexyl phenyl ketone (10 mg) were added to the solution as a photocrosslinker and photoinitiator, respectively. Finally, the mixture was transferred to a UV lamp with a wavelength of 365 nm for 600 s of rapid photocrosslinking.

[0098] 2. Observation of composite hydrogel morphology

[0099] (1) The microstructure of the composite hydrogel was observed using a scanning electron microscope.

[0100] (2) Figure 6 As shown, the composite hydrogel has a three-dimensional network structure.

[0101] 3. Swelling curve of composite hydrogel

[0102] (1) Make a circular hydrogel sample (W) using a mold d ), immersed in PBS solution, and the hydrogel was kept at 37°C, and the mass (W) was measured at specific time intervals. t ), calculation formula: Swelling rate (%) = W d / W t ×100%.

[0103] (2) Changes in the swelling properties of the composite hydrogel over time Figure 7 The samples of all concentrations basically reached swelling equilibrium within 4 hours, and the swelling rate did not increase significantly after 24 hours.

[0104] 4. Investigation of water vapor permeability of composite hydrogel

[0105] (1) Weigh the bottle containing pure water (w1, g) and seal the bottle mouth with hydrogel (5 mm thick). Then place the sealed bottle in a 37°C, 50% humidity comprehensive stability test chamber for 24 hours (t, h), then take it out immediately and weigh it again (w2, g). Finally, measure the area of ​​the bottle mouth and record it as S (m 2 ). The calculation formula is: water vapor transmission rate (WVTR) = (w1-w2) / t×S.

[0106] (2) From Figure 8 It can be seen from the results that the porosity of the composite hydrogel gradually decreases with the increase of the concentration of biological ionic liquid, which is consistent with the SEM results.

[0107] 5. Investigation of the porosity of composite hydrogels

[0108] (1) The porosity of the hydrogel sample was determined by the ethanol substitution method. First, weigh the mass of a 10 mL centrifuge tube containing 5 mL of anhydrous ethanol (m1, g), and accurately mark the lowest point of the liquid surface with a pen. Then, soak the composite hydrogel (m0) in ethanol. Ultrasonic treatment is performed until the pores of the hydrogel are completely filled with ethanol. Then, adjust the liquid level to the marked black line, and weigh the mass of the centrifuge tube containing ethanol and hydrogel (m2, g). Finally, quickly remove the hydrogel and weigh the mass of the centrifuge tube and the remaining ethanol (m3, g). The porosity of the hydrogel (P, %) is calculated by the following formula. P (%) = (m2-m3-m0) / (m1-m3) × 100%

[0109] (2) Due to its hydrophilicity and porous structure, the composite hydrogel has good water vapor permeability (e.g. Figure 8 shown).

[0110] 6. Investigation of blood compatibility of composite hydrogel

[0111] (1) Prepare composite hydrogels with different concentrations, extract with physiological saline to obtain extracts with different concentrations. Then, incubate the extract with rat red blood cells (RBCs, 2% v / v) at 37°C for 3 hours. The red blood cell suspension treated with physiological saline was used as a negative control, and the red blood cell suspension treated with pure water was used as a positive control. After the incubation, the product was centrifuged at 13000rpm for 5 minutes, and the absorbance of the supernatant was measured at 545nm. Each group was measured three times in parallel. The hemolysis ratio (Hemolysis ratio, %) is calculated as follows:

[0112]

[0113] (2) Fig. 9 As shown, the hemolysis rate of the composite hydrogel is much less than 5%, and it has good blood compatibility.

[0114] 7. Investigation of the antibacterial effect of composite hydrogel

[0115] (1) Composite hydrogels of different concentrations were prepared and the antibacterial activity of the composite hydrogels was investigated by plate method. The composite hydrogels were added to a 24-well plate (10 6 After co-culture at 37°C for 24 h, 100 μL of the bacterial suspension was spread on an MH medium agar plate and cultured at 37°C for 24 h. The number of colonies on each plate was observed.

[0116] (2) Fig.10 As shown in the intuitive figure, the composite hydrogel has a strong killing effect on Escherichia coli and Staphylococcus aureus, indicating that the composite hydrogel has good antibacterial activity.

[0117] 8. Investigation of the dynamic coagulation effect of composite hydrogel

[0118] (1) The composite hydrogels were placed in culture dishes and preheated at 37°C for 5 min. Then, 100 μL of fresh rat whole blood containing EDTA-K2 was slowly added to the surface of the hydrogel, and then 20 μL of CaCl2 (0.2M) solution was immediately added to start coagulation. After incubation at 37°C for 5 min, 25 mL of distilled water was slowly poured into the culture dish, and oscillated at 37°C (60 rpm) for 5 min. 200 μL of the solution was transferred to a 96-well plate and the absorbance was measured at 540 nm using an enzyme reader. The culture dish with the same operation but without the composite hydrogel was used as the control group. The calculation formula is as follows:

[0119]

[0120] (2) Fig.11 As shown, compared with the gauze group, the composite hydrogel significantly improved the in vitro coagulation rate.

[0121] 9. Investigation of in vitro hemostatic properties of composite hydrogel

[0122] (1) The hemostatic ability of the prepared hydrogel was evaluated using a rat tail amputation model. Six SD rats (200-280 g) were selected and randomly divided into two groups. After being weighed, they were anesthetized with 10% chloral hydrate (intraperitoneal injection, 5 mL / kg). A mark was made 3 cm from the tip of the rat's tail and the tail was cut with scissors. After 1 minute of uncontrolled bleeding, the hydrogel was immediately applied to the amputated tail, and the excess blood was absorbed from the bottom with pre-weighed multi-layer filter paper. The control group was treated with gauze.

[0123] (2) From Fig.12 It can be found that the composite hydrogel is stably attached to the bleeding site without falling off. And the hemostatic effect of the composite hydrogel is better than that of gauze.

[0124] 10. Investigation of wound healing effect of composite hydrogel

[0125] (1) This study used SD rats as a model to evaluate the wound healing performance of composite hydrogels. All rats (200-280g) were randomly divided into a control group and a composite hydrogel group, with 3 rats in each group. Anesthesia was performed by inhalation of ether gas in a closed chamber. After anesthesia, the back of the rat was depilated, and then a full-thickness wound with a diameter of about 15mm was cut on its back with surgical scissors. The wounds of rats in the hydrogel group were treated with composite hydrogel, while those in the control group were not treated. Optical images of the wound were recorded at 0, 3, 6, 9, 12, and 15 days after treatment. Professional software (ImageJ 1.8.0) was used to accurately measure the wound area. The wound healing rate (wound healing ratio, %) was calculated as follows:

[0126]

[0127] (2) Fig.13 As shown, the wound healing speed of the composite hydrogel group was always faster than that of the blank group, and after 15 days of treatment, the wound healing rate of the composite hydrogel group almost reached 100%.

[0128] Example 2

[0129] Preparation of composite hydrogel

[0130] The preparation process is the same as that of Example 1, except that the preparation of the biological ionic liquid is changed to 5 g of biological ionic liquid and 5 g of water. The prepared composite hydrogel has excellent properties.

[0131] Example 3

[0132] Preparation of composite hydrogel

[0133] The preparation process is the same as that of Example 1, except that the preparation of the biological ionic liquid is changed to 2.5 g of biological ionic liquid and 7.5 g of water. The prepared composite hydrogel has excellent properties.

[0134] Example 4

[0135] Preparation of composite hydrogel

[0136] The preparation process is the same as that of Example 1, except that the preparation of the biological ionic liquid is changed to 0.2 g of biological ionic liquid and 9.8 g of water. The prepared composite hydrogel has excellent properties.

Claims

1. A composite hydrogel based on bio-ionic liquid polymerization, characterized in that: The composite hydrogel has a three-dimensional network structure and is specifically prepared by the following steps: diluting the biological ionic liquid with water, stirring evenly, obtaining a clear and uniform solution A as a solvent for the reaction; evenly mixing methacrylic hyaluronic acid and oxidized hyaluronic acid to obtain a mixture B; slowly adding the mixture B to the solution A, stirring evenly, obtaining a mixture C; adding the ε-polylysine solution to the mixture C, mixing evenly, obtaining a mixture D; adding a photoinitiator and a photocrosslinker to the mixture D, mixing evenly, obtaining a mixture E; placing the mixture E under an ultraviolet lamp for crosslinking, wherein, The mass ratio of the methacryloyl hyaluronic acid to the oxidized hyaluronic acid is 7:1 to 7:2; the mass ratio of the methacryloyl hyaluronic acid to the ε-polylysine is 7:1 to 7:2; the mass ratio of the methacryloyl hyaluronic acid to the biological ionic liquid is 7:1 to 7:37.

5. The biological ionic liquid is prepared by the following method: choline hydroxide and acrylic acid are mixed and reacted; the product is washed with an organic solvent for multiple times and vacuum dried to obtain the product; wherein the molar ratio of choline hydroxide to acrylic acid is 1:1 to 1:2, the reaction temperature of the reaction is 4°C, and the reaction time is 24 hours; the organic solvent is ether and ethyl acetate.

2. The composite hydrogel according to claim 1, characterized in that: The mass ratio of the biological ionic liquid to water is 1:49 to 3:

1.

3. The composite hydrogel according to claim 1, characterized in that: The photocrosslinking time is 600s, the wavelength is 365nm; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, the photocrosslinker is polyethylene glycol diacrylate; the concentration of the ε-polylysine solution is 0.5g / mL.

4. The composite hydrogel according to claim 1, characterized in that: The methacryloyl hyaluronic acid is prepared by the following method: adding methacrylic anhydride to a hyaluronic acid solution for reaction, the reaction condition is an ice bath, and the pH of the reaction system is maintained in the range of 8-10; after the reaction is completed, the reaction solution is dialyzed and freeze-dried to obtain, The concentration of hyaluronic acid in the hyaluronic acid solution is 0.1-0.2 g / mL, and the hyaluronic acid solution is a mixed solution composed of water and N,N-dimethylformamide in a volume ratio of 3:2; the molar ratio of hyaluronic acid to methacrylic anhydride is 1:3-1:

10.

5. The composite hydrogel according to claim 1, characterized in that: The oxidized hyaluronic acid is prepared by the following method: sodium periodate is added to a hyaluronic acid aqueous solution for reaction at room temperature and in the dark; after the reaction is completed, the reaction solution is dialyzed and freeze-dried to obtain: The concentration of hyaluronic acid in the hyaluronic acid aqueous solution is 0.1-0.2 g / mL, and the molar ratio of hyaluronic acid to sodium periodate is 1:0.25-1:1.

Citation Information

Patent Citations

  • Biodegradable medical adhesive or sealant composition

    CN106061518A

  • Method for improving anti-calcification and anticoagulant activity of bioprosthetic valve material through double-bond post-crosslinking

    CN114748695A